2016
DOI: 10.1111/joic.12264
|View full text |Cite
|
Sign up to set email alerts
|

Active Versus Passive Anchoring Vascular Closure Devices Following Percutaneous Coronary Intervention: A Safety and Efficacy Comparative Analysis

Abstract: AngioSeal and Mynx appear to be equally safe and efficacious VCDs following PCI. The passive anchoring system may prove desirable as no intra-arterial anchor remains upon device removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…11 We reported a technical success rate of 97% (97/100), in both antegrade and retrograde cases. Compared to more established closure devices used in clinical practice, Angioseal technical success rates range from 69.2% to 98.7% [12][13][14][15] ; Starclose, 69.3-95.1% [14][15][16][17] ; and Proglide, 89.1-99.2%. [17][18][19] Mynx Control proved to be reliable in achieving haemostasis, especially in our high-risk cohort where we used the device immediately following completion of intended treatment, irrespective of the ACT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 We reported a technical success rate of 97% (97/100), in both antegrade and retrograde cases. Compared to more established closure devices used in clinical practice, Angioseal technical success rates range from 69.2% to 98.7% [12][13][14][15] ; Starclose, 69.3-95.1% [14][15][16][17] ; and Proglide, 89.1-99.2%. [17][18][19] Mynx Control proved to be reliable in achieving haemostasis, especially in our high-risk cohort where we used the device immediately following completion of intended treatment, irrespective of the ACT.…”
Section: Discussionmentioning
confidence: 99%
“…Proglide had 1.5% minor and 0.7% major complications, compared to the 1.9% and 3.7% of Starclose. Baker, N et al 13 reported a haematoma rate of 1.9% following Angioseal use in patients undergoing percutaneous coronary intervention (PCI).…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Transfemoral access site complications in noncoagulopathic patients is quoted at 3% for clinically significant hematoma and 2% risk of thrombotic complication. 19 Moreover, patients with elevated INR (>1.6) undergoing vascular interventions via transfemoral access have demonstrated significant retroperitoneal hematoma, requiring open surgical intervention in 2.4% of such patients. 20 Additionally, TRA provides the added technical advantage of ease of cannulation into a mesenteric artery owing to their sharp downward angulation.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) v analýze pacientů podstupujících perkutánní koronární intervenci (PCI) s použitím systémů Mynx a Angio-Seal zjistili, že bezpečnost a účinnost obou systémů je podobná u obou skupin. 2,22 Systém Prostar je určen k použití v kombinaci s pouzdry 8,5 Fr až 24 Fr, 23 proto by jeho použití v našem případě, kde byl zaveden 7Fr CŽK, nebylo vhodné. Navíc se jedná o systém založený na uzavření tepny pomocí stehů, které by vzhledem k anatomické lokalizaci nemusely být k použití vhodné podobně, jak bylo zmíněno výše u systému Perclose.…”
Section: Diskuseunclassified